SOME NOTES ON THE OLD MARKET LA CONCEPCION, LIMA CENTRAL MARKET TODAY - Coello Rodríguez, Antonio (2014)
In this text, prior to the construction of the old Mercado de La Concepción history is analyzed, current today Lima Central Market “Ramón Castilla”. Using newspapers of the time, we can tell as the daily life of the first Lima market, who lived and who their characters, as the day wore on, that was offered and how it was developed everyday. An important fact is the Chinese settler, who settled near the market place in which to develop their daily lives and offered their products, not knowing that on that place, will be located in Chinatown today.